Portable Measurement Systems Based on Microcontrollers to Test Durability of Structures: Mini-Review - Segura, Crhistian C.; Osma, Johann F. (Frontiers in Built Environment, 2020)
Corrosion presence is a recurrent concern in buildings and structures that use steel as its core or as reinforcement, due to the change of steel's properties caused by this phenomena. Therefore methods to detect and quantify corrosion had been developed; some are based on electrical and electrochemical measurements. On reinforced concrete structures, sometimes there are exposed steel bars at sight, but on those, a visual inspection could determine corrosion presence. There exist different options to measure the steel bars' corrosion and its level. The more straight forward consists of cutting through the concrete until the bar is exposed and connect a measurement device there. A disadvantage of this technique is that steel has to be exposed to the environment during the measurement; as an alternative, novel contact-less electrochemical techniques are getting more popular. Recent advances in low-cost and portable electrochemical devices and embedded sensors can change how the structures are tested. Moreover, there is a discussion about how those devices developed for other fields as biosensors can assist in other areas. This mini-review also gives some hints of what could be future trends due to the joint of those areas.